Archetypes and Mythological Motifs: John Updike’s Legacy Revisited - Ulvydienė, Loreta (Respectus Philologicus, 2018)
John Updike is widely considered to be one of the greatest, one of the most popular and sometimes most controversial writers concerned with the American small town and middle-class materialism. A lot of literary critics and researchers observe that Updike’s finest work came from his exploration of ordinary America and from his use of elegant prose, rich with metaphor, to portray the public and private feelings of Americans, their daily rounds of life. In addition, discussing Updike’s individual works a lot of literary critics and researchers have observed the writer’s attempts to re-write myth in “the mythical age”1 of the 20thcentury. Naturally enough, as the return to myth is assumed to be a certain feature of the Modernist movement, half a century later since Updike’s famous novel Centaur was penned, it is indispensable to re-examine the writer’s fictional intentions in the usage of myth. More importantly, it is needful to determine whether we can see the mythic elements and realistic details as a continuum or as the contrasted opposites in his so called “historical chronicles”. Updike’s novels and stories are filled with mythological motifs and character archetypes. Thus, the study aims at revisiting John Updike’s creation considering mythological elements and archetypal images of his heroes alongside with heroic masculinity, war, terrorism and American perfectionism.
Keywords: Myth; Archetype; Mythology of Self; Masculinity; Dichotomy; Other